Understanding Inflammatory Responses in the Manifestation of Prothrombotic Phenotypes - Chanchal, Shankar; Mishra, Aastha; Singh, Manvendra Kumar; Ashraf, Mohammad Zahid (Frontiers in Cell and Developmental Biology, 2020)
Inflammasome complex is a multimeric protein comprising of upstream sensor protein of nucleotide-binding oligomerization domain (NOD)-like receptor family. It has an adaptor protein apoptosis-associated speck-like protein and downstream effector cysteine protease procaspase-1. Activation of inflammasome complex is body’s innate response to pathogen attack but its abnormal activation results in many inflammatory and cardiovascular disorders including thrombosis. It has displayed a prominent role in the clot formation advocating an interplay between inflammation and coagulation cascades. Therefore, elucidation of inflammasome and its molecular mechanisms in the manifestation of prothrombotic phenotypes becomes pertinent. Thrombosis is the formation and propagation of blood clot in the arterial or venous system due to several interactions of vascular and immune factors. It is a prevalent pathology underlying disorders like venous thromboembolism, stroke and acute coronary syndrome; thus, making thrombosis, a major contributor to the global disease burden. Recently studies have established a strong connection of inflammatory processes with this blood coagulation disorder. The hemostatic balance in thrombosis gets altered by the inflammatory mechanisms resulting in endothelial and platelet activation that subsequently increases secretion of several prothrombotic and antifibrinolytic factors. The upregulation of these factors is the critical event in the pathogenesis of thrombosis. Among various inflammasome, nucleotide-binding domain, leucine-rich-containing family, pyrin domain containing 3 (NLRP3) is one of the best-studied sterile inflammasome strengthening a link between inflammation and coagulation in thrombosis. NLRP3 activation results in the catalytic conversion of procaspase-1 to active caspase-1, which facilitate the maturation of interleukin-1β (IL-1β) and interleukin-18. These cytokines are responsible for immune cells activation critical for immune responses. These responses further results in endothelial and platelet activation and aggregation. However, the exact molecular mechanism related to the pathogenesis of thrombosis is still elusive. There have been several reports that demonstrate Tissue factor (TF)-mediated signaling in the production of pro-inflammatory cytokines enhancing inflammation by activating protease-activated receptors on various cells, which lead to additional cytokine expression. Therefore, it would be illuminating to interpret the inflammasomes regulation in coagulation and inflammation. This review, thus, tries to comprehensively compile emerging regulatory roles of the inflammasomes in thrombosis and discusses their molecular pathways in the manifestation of thrombotic phenotypes.